2009
DOI: 10.1097/meg.0b013e3283086757
|View full text |Cite
|
Sign up to set email alerts
|

Clinical meaning of pepsinogen test and Helicobacter pylori serology in the health check-up population in Korea

Abstract: The H. pylori IgG status, age, and sex were associated with the serum PG levels. To increase the efficacy of the PG I/II ratio for the detection of atrophic gastritis, the cutoff value of the PG I/II ratio should be stratified according to the H. pylori IgG status in the Korean population presenting for a health check-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 33 publications
5
44
0
Order By: Relevance
“…It is assumed and also found in several studies [15], that PG test results directly correlate with H. pylori status in patients, based on the fact that H. pylori is the main etiological factor for atrophic changes in the gastric mucosa [5,8,17,18].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…It is assumed and also found in several studies [15], that PG test results directly correlate with H. pylori status in patients, based on the fact that H. pylori is the main etiological factor for atrophic changes in the gastric mucosa [5,8,17,18].…”
Section: Introductionmentioning
confidence: 88%
“…27 No 1: [11][12][13][14][15][16][17] At present, the gold standard for diagnosis of gastric mucosal changes is the biopsy performed during an upper gastrointestinal endoscopy followed by histological examination [3,6]. Evaluation of the histological status of the mucosa can be performed using the updated Sydney System, the Operative Link on Gastritis Assessment (OLGA) and the Operative Link for Gastric Intestinal Metaplasia assessment (OLGIM) systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as PG II exhibits a greater rise relative to PG I, [43][44][45] the PG I/II ratio decreases in the presence of H. pylori-infection (Fig. 1).…”
Section: H Pylori Infection and The Effect Of H Pylori Eradication mentioning
confidence: 99%
“…43,49-52 Kim et al 43 showed that male gender was associated with higher PG I than female but there was no correlation in case of PG II or PG I/II ratio in 1,485 healthy subjects (964 [64.9%] H. pylori positive cases). However, PG I was not associated with body mass index (BMI).…”
Section: The Effect Of Other Factors On Pepsinogen Levelsmentioning
confidence: 99%